Repeated sprint training in hypoxia delays fatigue during 30-sec all-out sprint and reduces blood lactate concentrations after exercise in trained cyclists: a case study - Takei, N.; Kakinoki, K.; Hatta, H. (The Journal of Physical Fitness and Sports Medicine, 2020)
Repeated sprint training in hypoxia (RSH) is a potential training strategy to improve short-term high-intensity sprint ability and evoke adaptation of lactate metabolism. Therefore, the purpose of the present study was to examine the effects of RSH on Wingate sprint performance and lactate metabolism. Eight university cyclists performed 6 sessions of RSH (3 × 30-sec sprint with 5-min recovery, FiO2: 14.5%) over 6 consecutive days. Two days before (pre-test) and 7-9 days after (post-test) the training intervention, subjects performed Wingate tests as performance tests. We took blood samples before and 0.5, 1, 2, 3, 4, 5, 7, 10 min after the Wingate test to evaluate physiological adaptations. Mean power outputs were unchanged after the intervention (p = 0.094, d = 0.23). Whereas, the fatigue index was significantly improved (p = 0.025, d = 0.43). According to time course change in power outputs during the Wingate test, power outputs at 26 s, 29 s and 30 s were significantly improved after the intervention (p = 0.029, 0.001 and 0.001; d = 0.54, 0.74 and 0.74, respectively). Area under the curve (AUC) of blood lactate concentration was significantly lowered after the intervention (p = 0.048, d = 0.46). Six sessions of RSH over 6 consecutive days delayed fatigue during the Wingate test. AUC of blood lactate concentration was lowered after the intervention, indicating that glycogen breakdown was reduced (glycogen sparing effect) and/or lactate oxidation was increased during and after the Wingate test when the same work was performed. The effects of glycogen sparing and increased lactate oxidation would provide a competitive advantage to athletes performing multiple sprints.